2015
DOI: 10.1002/nbm.3348
|View full text |Cite
|
Sign up to set email alerts
|

MRI accurately identifies early murine mammary cancers and reliably differentiates between in situ and invasive cancer: correlation of MRI with histology

Abstract: MRI methods that accurately identify various stages of mouse mammary cancer could provide new knowledge that directly impacts management of breast cancer in patients. This research evaluates whether MRI can accurately follow the progression from in situ to invasive cancer, by evaluating in vivo and ex vivo MRI, and compared to histology as the gold standard for diagnosing and staging cancer. Six C3(1)SV40Tag virgin female mice between the age of 12-16 weeks were studied. At this age, these mice develop in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…On the other hand, MRI provides excellent soft tissue contrast, can detect early cancer in vivo much more reliably than other imaging modalities, allows evaluation of the surrounding parenchyma, and allows accurate tumor volume measurements over time. Previous work from our laboratory demonstrated that in vivo T 2 ‐weighted MRI reliably detects very early in situ mammary tumors in SV40TAg mice with high sensitivity and specificity, and differentiates in situ from invasive cancer . Precise correlations between in vivo MR and histology images have also been demonstrated .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…On the other hand, MRI provides excellent soft tissue contrast, can detect early cancer in vivo much more reliably than other imaging modalities, allows evaluation of the surrounding parenchyma, and allows accurate tumor volume measurements over time. Previous work from our laboratory demonstrated that in vivo T 2 ‐weighted MRI reliably detects very early in situ mammary tumors in SV40TAg mice with high sensitivity and specificity, and differentiates in situ from invasive cancer . Precise correlations between in vivo MR and histology images have also been demonstrated .…”
Section: Introductionmentioning
confidence: 75%
“…The right inguinal gland from each mouse was chosen for ex vivo MRI and histology. The selected gland was then excised from the skin and placed between two layers of pathology foam, mimicking the exact position of the ex vivo mammary gland on the skin, and the exact position of the mammary gland in hematoxylin and eosin (H&E)‐stained slices, as previously described . Since the ex vivo gland was scanned by MRI in the same orientation as the H&E‐stained tissue, the ex vivo MR images served as a ‘bridge’ between in vivo MRI and histology to facilitate accurate correlation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on size criteria defined for in situ and invasive cancers as previously published [16], we identified a total of 31 in situ cancers and 10 invasive tumors (Table 1) in the inguinal mammary glands of eight SV40 mice by examining all MRI slices through the glands. No cancers were found in the FVB/N mice.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, all FVB/N mice were injected on the right side, four SV40 mice were injected on right side, and four were injected on the left side. A cancer was classified as in situ when its size was between 150 – 400 microns, and classified as invasive if its size was >400 microns in largest diameter, based on previous work from this group that correlated cancers on MRI with histology [16]. …”
Section: Methodsmentioning
confidence: 99%